2016
DOI: 10.1111/desc.12419
|View full text |Cite
|
Sign up to set email alerts
|

Segmenting words from fluent speech during infancy – challenges and opportunities in a bilingual context

Abstract: Previous research shows that word segmentation is a language-specific skill. Here, we tested segmentation of bi-syllabic words in two languages (French; English) within the same infants in a single test session. In Experiment 1, monolingual 8-month-olds (French; English) segmented bi-syllabic words in their native language, but not in an unfamiliar and rhythmically different language. In Experiment 2, bilingual infants acquiring French and English demonstrated successful segmentation for French when it was tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 68 publications
3
32
1
Order By: Relevance
“…How do we reconcile our current results with Polka et al. (), which showed that bilingual infants have difficulty segmenting in both of their native languages? There are several methodological differences between these two studies which may explain the discrepancy of results.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…How do we reconcile our current results with Polka et al. (), which showed that bilingual infants have difficulty segmenting in both of their native languages? There are several methodological differences between these two studies which may explain the discrepancy of results.…”
Section: Discussionsupporting
confidence: 79%
“…Our current study shows the same type of processing with a dual-language stream of English and French, indicating that this skill holds validity in a natural language context. How do we reconcile our current results with Polka et al (2017), which showed that bilingual infants have difficulty segmenting in both of their native languages? There are several methodological differences between these two studies which may explain the discrepancy of results.…”
Section: Bilingual Infants' Processing Capacitysupporting
confidence: 59%
See 3 more Smart Citations